Kehidupan Baru dalam Kristus: Eksegesis Teks 2 Korintus 5:17 - Juanta, Elkria (Vieka Wahana Semesta, 2025)
This study offers a comprehensive exegesis of 2 Corinthians 5:17, a key verse in Paul's theology concerning the transformation brought about by the gospel. Although traditional interpretations tend to limit the new creation (kainē ktisis) to individual (anthropological) transformation, the main argument of this study is that the concept should be understood multidimensionally, which also includes eschatological (cosmological) and communal (ecclesiological) dimensions. Using an integrated exegetical approach (historical-critical, grammatical-lexical, and intertextual), this study shows that the new creation is a cosmic reality inaugurated by Christ that is first realized in believers and then manifested in the Church community. A lexical analysis of the term kainē shows that this transformation is an act of divine qualitative creation, not merely an improvement in human morality. The results obtained in this study confirm that becoming a new creation is a grace that binds believers to the death and resurrection of Christ (ἐν Χριστῷ) and has strong pastoral implications. The new creation is motivated to engage in the mission of reconciliation, to continually experience renewal of mind, and to maintain a life of spiritual discipline in grateful response to its new identity.